2019
DOI: 10.1111/jdv.15880
|View full text |Cite
|
Sign up to set email alerts
|

Basal cell carcinoma genetic susceptibility increases the rate of skin ageing: a Mendelian randomization study

Abstract: BackgroundOnset of basal cell carcinoma (BCC) is connected to skin ageing, but it is unclear whether higher BCC genetic susceptibility drives skin ageing.ObjectivesTo investigate whether loci increasing genetic susceptibility to BCC also drive multiple features of skin ageing, independently of confounding factors, using Mendelian randomization.MethodsA Mendelian randomization study was conducted in older adults from the Leiden Longevity Study (N = 604). A total of 25 BCC loci, selected based on a published gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…Importantly, in the context of GWAS, a significance threshold of 1e-5 is not conventionally recognized. [25][26][27] Although 1e-5 is a compromise threshold in microbiome-wide association studies (mGWAS), this should be acknowledged due to potential weak instrument bias. Notably, our study set the F-statistic threshold above 10 to mitigate the impact of weak statistical variables, a common practice in gut microbiota research adopting 1e-5 as a significance threshold.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Importantly, in the context of GWAS, a significance threshold of 1e-5 is not conventionally recognized. [25][26][27] Although 1e-5 is a compromise threshold in microbiome-wide association studies (mGWAS), this should be acknowledged due to potential weak instrument bias. Notably, our study set the F-statistic threshold above 10 to mitigate the impact of weak statistical variables, a common practice in gut microbiota research adopting 1e-5 as a significance threshold.…”
Section: Discussionmentioning
confidence: 99%
“…However, the findings should be interpreted cautiously due to limitations such as the reliance on summarized data, or potential population stratification biases. Importantly, in the context of GWAS, a significance threshold of 1e‐5 is not conventionally recognized 25–27 . Although 1e‐5 is a compromise threshold in microbiome‐wide association studies (mGWAS), this should be acknowledged due to potential weak instrument bias.…”
Section: Discussionmentioning
confidence: 99%
“…Skin cancer is one of the top over-represented categories associated with facial aging. Interestingly, a recent independent study on another cohort (Leiden Longevity) found that mechanisms influenced by genetic loci increasing susceptibility to basal cell carcinoma also drive skin ageing suggesting shared biology and shared targets for interventions [35].…”
Section: Discussionmentioning
confidence: 99%
“…The inverse‐variance‐weighted (IVW) model was utilized as the core random‐effects analysis method, which is most extensively used and could offer robust causal evaluations in the context of the absence of directional pleiotropy 16 . After the Bonferroni correction, p < 0.0125 (0.05/4) was identified as significant, while associations with p ≥ 0.0125 and <0.05 were considered as suggesting significance 17 .…”
Section: Methodsmentioning
confidence: 99%
“…The inverse-variance-weighted (IVW) model was utilized as the core random-effects analysis method, which is most extensively used and could offer robust causal evaluations in the context of the absence of directional pleiotropy. 16 After the Bonferroni correction, p < 0.0125 (0.05/4) was identified as significant, while associations with p ≥ 0.0125 and <0.05 were considered as suggesting significance. 17 Besides, we used odds ratios (ORs) with 95% confidence intervals (CIs) to present the effect estimates, which can be explained as the average variation in the outcome per log-odds increase in the genetically predicted risk of the respective binary exposure.…”
Section: Statistical Analysesmentioning
confidence: 99%